Matemática financeira : um conhecimento importante e necessário para a vida das pessoas - Schneider, Ido José (2008)
This study had as objective to question and analyze the importance of financial mathematics contents to people s lives, showing the necessity of taking possession of the meanings of this contents, to making appropriate and conscious decisions facing the facilities in credit provided by the trade market and financial companies. As an instrument of information collection there was the use of questionnaires, applied to students of 8th grade and senior year and also to math teachers of the municipal schools of Marau/RS, and documents that registered real shopping, loaning and financing situations offered in commercial establishments and financial institutions. The data was analyzed based on theories, researches and documents related to the theme, using a qualitative approach. The analysis indicated a fragmented, incomplete and superficial knowledge, by the difficulty of the students in remembering something about each of the financial mathematics contents studied at school. Even though the totality of students and teachers questioned consider important the knowledge of this contents to people s lives, this part of math is not receiving priority in basic education, especially in high school, because they are only in a few didactic books. The real situations show the necessity of the knowledge of the financial mathematics contents, not to be caught in the traps of credit plans and easy credit. Based on observations of this study, comes the suggestion of contextualized study, using informative material from people s day to day lives like newspaper articles, magazines, promotional folders related to the concepts of financial mathematics that provides a financial education to the students.